Oxidation studies of Al alloys: Part I Al-Cu (liquid phase) alloy. (15th August 2019) - Wu, G.; Dash, K.; Galano, M.L.; O'Reilly, K.A.Q.
Highlights: Evolution of CuAl2 in the oxidation process is studied by hot stage microscopy. Oxides' nature was identified through isolation of oxides. Sequence of oxidation: amorphous γ-Al2 O3 -crystalline γ-Al2 O3 -crystalline α-Al2 O3 . Sequence of oxidation in Al-5Cu alloy identified for the first time. Al-5Cu alloy shows a pseudo-parabolic oxidation behaviour in 450–650 °C. Abstract: This unique investigation explores the nature and chemistry of the oxides on Al-Cu alloys in the liquid state and conducts thermodynamic simulations and kinetic studies of the oxidation process. The morphology, microstructural evolution and chemistry of the oxides were explained over different time intervals. Thermodynamic simulations were performed to explain the formation and stability of oxides in the Al-5Cu alloy; the oxidation mechanism was discussed and compared to that of pure Al. Between 450–650 °C, the oxidation kinetics of Al exhibit parabolic and Al-5Cu shows pseudo-parabolic behaviour whereas between 750–950 °C both follow linear rate equations with activation energies of 150–200 kJ mol −1 .